The Influence of Service Quality and Price Perception on Customer Loyalty with Customer Satisfaction as an Intervening Variable at Tazkia Tour Umrah and Hajj Travel Agency - Rahmawati, Reni; Andika, Afri; Pawirosumarto, Suharno (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of service quality and price perception on customer loyalty, with customer satisfaction as a mediating variable, at Tazkia Tour Umrah and Hajj Travel Agency. A total of 81 respondents who had used the agency’s services were surveyed using a structured questionnaire. Data were analyzed with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results indicate that service quality has a positive and significant effect on customer satisfaction, and price perception also has a positive and significant effect on customer satisfaction. Service quality further demonstrates a significant direct effect on customer loyalty, while price perception does not directly influence loyalty. Customer satisfaction has a strong and significant effect on loyalty, acting as a partial mediator in the relationship between service quality and loyalty, and as a full mediator between price perception and loyalty. The R-Square results show that customer satisfaction is explained by service quality and price perception at 50.3%, while customer loyalty is explained by service quality, price perception, and customer satisfaction at 72.5%. These findings highlight the importance of enhancing service quality and ensuring fair and transparent pricing to strengthen customer satisfaction, which in turn fosters long-term customer loyalty. The study contributes to both theoretical development in service marketing and practical implications for managing Umrah and Hajj travel services.